(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purchasing nature or behavioral attributes of the final buyer are known as Consumer Buying Behavior. There are several aspects, particular features and dimensions to impact a purchaser’s decision to buy something, his or her purchasing nature, habits during buying, preferences for specific brands or retail stores etc. These factors in combination lead to a buying decision. Besides, cultural aspects, social status, membership groups, financial spot in the economy ladder, his or her individuality, family, surrounding aspects as well as mentality are crucial features to shape the decision as well. Through recognizing and comprehending these aspects about clients and consumers, brands can put up a plan, a marketing strategy (Unique Value Proposition) as well as promotions and deals to be more suitable as per the demands and requirements of target clients. This is the actual method or fulfilling the demands of a customer and in turn, boosts their sales.